Pengaruh Pendidikan Keluarga Islami Terhadap Pembentukan Karakter Anak - Najamudin (Jurnal Dirosah Islamiyah, 2024)
Islamic family education has an important role in shaping children's character. The spiritual and moral values taught in an Islamic family environment become the main foundation in shaping good character in children. This article aims to explore the influence of Islamic family education on children's character formation. Through the literature study method, data was collected to analyse the Islamic values emphasised in family education and their impact on children's character. The results show that Islamic family education makes a positive contribution in shaping children's character, including values such as sincerity, honesty, patience and caring. In conclusion, Islamic family education has a significant role in shaping children's character in accordance with the teachings of Islam.